Movement characteristics studies of the fresh and frozen-thawed hyperactivated and acrosome-reacted goat sperm using computer-assisted semen analyzer - Abdullah, Ramli; Mat Noor, M.; Hashida, N.H.; Rajikin, M.H. (2005)
Sperm motility is believed to be one of the most important parameters for evaluating male fertility potential. Data pertaining to the movement characteristics using computer-assisted semen analyzer (CASA) in hyperactivated and acrosome-reacted goat sperm are lacking. Therefore, in the current study, fresh and frozen-thawed of goat sperm movement characteristics for the washed, washed hyperactivated and washed acrosome-reacted sperm were presented. The sperm were cooled slowly at 4°C for 3.5 hours before being plunge into liquid nitrogen. The fresh washed and frozen-thawed washed sperm were then subjected to treatment with heparin for hyperactivation and calcium ionophore for acrosome reaction. The average path velocity (VAP), straight line velocity (VSL), curvilinear velocity (VCL), beat cross frequency (BCF), straightness (STR) and linearity (LIN) in washed, washed hyperactivated and washed acrosome-reacted fresh and frozen-thawed sperm were found to be significantly higher compared to fresh control. We concluded that the digital imaging system can adequately and rapidly quantitate a large number of sperm cells with heterogeneous motility patterns. This technique may prove to be useful in defining movement characteristic associated with capacitation, acrosome reaction and fertilizing capacity of human sperm.